2023
DOI: 10.1002/mco2.265
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and targeting resistance mechanisms in cancer

Abstract: Resistance to cancer therapies has been a commonly observed phenomenon in clinical practice, which is one of the major causes of treatment failure and poor patient survival. The reduced responsiveness of cancer cells is a multifaceted phenomenon that can arise from genetic, epigenetic, and microenvironmental factors. Various mechanisms have been discovered and extensively studied, including drug inactivation, reduced intracellular drug accumulation by reduced uptake or increased efflux, drug target alteration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 434 publications
0
16
0
Order By: Relevance
“…In addition, our results demonstrated that deguelin effectively resensitized the paclitaxel in SKOV3-TR cells by activating the intrinsic apoptosis pathway through downregulation of antiapoptotic factors, including BCL-2 and MCL-1. According to several studies showing the role of EGFR signaling in conferring chemoresistance to various anticancer drugs, including cisplatin in various carcinomas, 26,134,135 deguelin holds promise for combating chemoresistance in EGFR-positive cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results demonstrated that deguelin effectively resensitized the paclitaxel in SKOV3-TR cells by activating the intrinsic apoptosis pathway through downregulation of antiapoptotic factors, including BCL-2 and MCL-1. According to several studies showing the role of EGFR signaling in conferring chemoresistance to various anticancer drugs, including cisplatin in various carcinomas, 26,134,135 deguelin holds promise for combating chemoresistance in EGFR-positive cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…[125] A prominent challenge that a majority of patients with solid tumors are facing is the diminished responsiveness of the TME in both primary and metastatic tumors, primarily attributed to constrained drug delivery and heightened levels of immunosuppression. [126] In this perspective, scholars delve into how various nanomedicines and strategies for TME modulation can effectively contribute to advancing the cancer immune cycle. Beyond facilitating the encapsulation of diverse immunostimulatory drugs, chemotherapeutics, and radiosensitizers, specific organic or inorganic NPs that are endowed with distinct physicochemical properties hold the potential to sensitize the immune system.…”
Section: Immunomodulatory Npsmentioning
confidence: 99%
“…A counterbalance to this phenomenon is the use of synergistic therapy, which is based on the utilization of two or more drugs that interact with each other based on additive synergy (the drugs have the same mechanism of action or a common target) and hyperadditive synergy (the drugs have different mechanisms of action or different targets, which makes the combined use of drugs more effective than the application of each one separately). Synergistic therapy allows for the optimization of treatment efficiency, overcoming the resistance of cancer cells, and reducing adverse effects [ 80 ].…”
Section: Naltrexonementioning
confidence: 99%